Measuring Willingness to Pay by Means of the Trade-off between Free Available Cash and Specific-Purpose Vouchers - Theo Lieven; Silke Lennerts (BuR - Business Research, 2013)
Primarily because of the hypothetical character of interview situations, respondents are often unable to state their true willingness to pay (WTP). This inability results in the so-called hypothetical bias. To address this bias, incentive-compatible methods have been proposed, but such methods are applicable only to real products. We propose a new method for measuring WTP based on disposable cash and specific purpose vouchers that are earmarked for particular goods that, contrary to incentive-compatible methods, can be used for hypothetical products and services that are less affected by the hypothetical bias. Empirical studies show that the new procedure provides WTP results that are equal to the results of alternative incentive-compatible elicitation procedures, such as the Vickrey auction and the BeckerDeGrootMarschak (BDM) procedure.
urn:nbn:de:0009-20-38088
Keywords: 650; hypothetical bias; incentive compatibility; stated preferences; willingness to pay